Modeling and Verification of Multi-Strut Modeling Approach of Masonry Panel Surrounded by RC Frame - Faisal, Fahim; Mirza, Md Rayhan; Afrin, Sadia; Sen, Debasish (Journal of Engineering Science, 2023)
Bangladesh which lies in an earthquake-prone region, possesses many seismically vulnerable structures and would need to be strengthened for future usage following the current building code. In this context, assessing the responses of the existing building frames with or without infilled masonry is essential for designing an adequate strengthening scheme that would be suitable for the building. The current study intends to model and simulate one of the available masonry infilled test specimens where the fiber modeling approach of RC member and the multi-strut model of infill masonry have been considered. In addition, the numerically obtained lateral strength has also been compared with analytically evaluated lateral strength. The lateral responses obtained from the numerical analysis showed a fair agreement with the experimental cyclic behavior having a ratio of experimental to the numerical lateral capacity of 0.97. The numerical lateral strength also indicates good conformity with analytical evaluation having an analytical to numerical lateral capacity ratio of 1.13. Journal of Engineering Science 13(2), 2022, 21-29